Guía para la adecuada ejecución presupuestal de los recursos de inversión asignados a la Secretaría de Educación del Distrito Capital (2011)
Education Policy of the city of Bogota in recent years has been based on ensuring the right to education and participation. The development of education falls under the general policies of the city whose purposes have been designed to strengthen democracy, reduce poverty and improve the quality of life for its inhabitants. At present the school care coverage with gratitude, subsidies, food, participation in recreational and leisure activities, with greater opportunities in higher education and better job opportunities are some of the most relevant with the passage of time has become major challenges for the Ministry of Education which is necessary to strengthen the management of individual investment projects through the budget. The Ministry of Education adopts the budget ordered by the Budget Statute that allows the efficient implementation of resources to advance the fulfillment of goals. Once approved the budget, the Ministry of Finance issues the resolution which sets the value for the force and sanctions the unexecuted value. According to the specification, we can conclude that the budget execution in the Ministry of Education has serious implications for the management, organization and commitment because it must meet the goals and objectives outlined in the National Development Plan. Finally notes that the Ministry of Education does not run the entire budget due to internal and external factors that are related to the planning and legal regulations that govern them, which implies that the program is not carried out in the terms that were designed